A Calibration Test for Latent Fingerprint Development on Thermal Paper. Issue 6 (17th July 2014) - Spencer, Caroline A.; Bond, John W.
Abstract A calibration test is described for monitoring the operation of equipment used to develop latent fingerprints on thermal paper by the application of either controlled or uncontrolled heat. A working solution of a water/glycerol emulsion and butylene glycol is applied to thermal paper by means of either a vinyl stamp and pad, or a marker pen. Varying the amount of butylene glycol enables the thermal paper to change color at different temperatures between approximately 40 and 60°C, which is below the normal color change temperature of the paper. The described test may be used to verify the correct operation, at different temperatures, of a controlled heat source during and after fingerprint development (such as the Hot Print System) or to monitor the paper temperature with an uncontrolled heat source (such as a warm air blower), thereby avoiding unintentional coloring of the entire paper surface.